Facilities that service economically advantaged neighborhoods perform surgical metastasectomy more often for patients with colorectal liver metastases. Issue 2 (22nd October 2019) - Uppal, Abhineet; Smieliauskas, Fabrice; Sharma, Manish R.; Maron, Steven B.; Polite, Blase N.; Posner, Mitchell C.; Turaga, Kiran
Abstract : Background: Metastasectomy of isolated colorectal liver metastases (CRLM) requires significant clinical expertise and may not be readily available or offered. The authors hypothesized that hospitals that treat a greater percentage of patients from higher income catchment areas are more likely to perform metastasectomies regardless of patient or tumor characteristics. Methods: Using the National Cancer Data Base, the authors classified facilities into facility income quartiles (FIQs) based on the percentage of patients from the wealthiest neighborhoods (by zip code). Quartile 1 included facilities with <2.1% of the patients residing within the highest income zip codes, quartile 2 included facilities with 2.2% to 15.6% of patients residing within the highest income zip codes, quartile 3 included facilities with 15.7% to 40.2% of patients residing within the highest income zip codes, and quartile 4 included facilities with 40.3% to 90.5% of patients residing within the highest income ZIP codes. Patient, tumor, and facility characteristics were analyzed using a multivariate logistic regression to identify associations between metastasectomy and FIQ. Results: Patients with CRLM were more likely to undergo metastasectomy at facilities in the highest FIQ compared with the lowest FIQ (18% vs 11% in FIQ4; P  = .001). This trend was not observed in the resection of primary tumors for nonmetastatic CRLM (rates of 95% vs 93%; P  = .94). After adjusting for individual insurance status, distance traveled, zip code–level individual income, tumor, and host, patients who were treated at the highest FIQ facilities were found to be more likely to undergo metastasectomy (odds ratio, 1.29; 95% CI, 1.02‐1.72 [ P  = .03]). Conclusions: Metastasectomy for CRLM is more likely to occur at facilities that serve a greater percentage of patients from high‐income catchment areas, regardless of individual patient characteristics. This disparity uniquely affects those patients with advanced cancers for which specialized expertise for therapy is necessary. Abstract : Facilities that serve patients from wealthier areas appear to perform more metastasectomies for colorectal liver metastases regardless of individual patient characteristics. This disparity uniquely appears to affect those patients with advanced cancers for whom specialized expertise for therapy is necessary.